A SURVEY ON THE RATE OF OSTEOPOROSIS TREATMENT AFTER PERCUTANEOUS VERTEBROPLASTY WITH BIOLOGIC CEMENT IN PATIENTS WITH THORACOLUMBAR VERTEBRAL COMPRESSION FRACTURES DUE TO OSTEOPOROSIS (Vietnam Journal of Community Medicine, 2026)
Introduction: Osteoporotic vertebral compression fractures cause prolonged back pain, reduced mobility, and a lower quality of life. Percutaneous vertebroplasty provides rapid pain relief, but the rate of post-operative osteoporosis treatment is inconsistent, which increases the risk of refracture.Objective: To survey the rate of osteoporosis treatment and identify factors associated it after percutaneous vertebroplasty in patients with thoracolumbar vertebral compression fractures due to osteoporosis.Methods: A cross-sectional descriptive study was conducted on 38 patients treated at the Department of Neurosurgery, Cho Ray Hospital from January 2024 to March 2025.Results and Discussion: Following percutaneous vertebroplasty, 100% of patients were prescribed Calcium and Vitamin D supplements. Although essential for general bone health, Calcium and Vitamin D have limited and inconsistent effects on reducing the risk of vertebral fractures in the elderly. Therefore, specialized anti-osteoporotic therapy is required. Our study found that 86.8% of patients received specialized treatment, including: oral Bisphosphonates 63.2% of patients, intravenous Bisphosphonates 21.1%, and Calcitonin 18.4%. Five patients did not receive anti-resorptive, bone-forming and dual-action medications for the following reasons: lack of counseling, financial constraints, and the cessation of pain after surgery.Conclusion: It is necessary to improve patient counseling regarding osteoporosis treatment to help them understand its importance. Additionally, collaboration between the Department of Musculoskeletal Internal Medicine and the Department of Neurosurgery is needed to enhance treatment effectiveness.
Keywords: vertebral compression fracture, osteoporosis, vertebroplasty.